Solving the food security crisis in South Africa: how food gardens can alleviate hunger amongst the poor - Earl, Alexandra (My University, 2011)
This report examines the food security crisis that exists in South Africa at the household level. It examines the global and local implications of the food crisis and the role of organic agriculture in creating food security in the future. This report selected a case study from the Botshabelo Township in the Free State Province. It examined how food gardens can help food security issues and thus improve hunger and malnutrition amongst participants